HUBUNGAN KAUSALITAS PENGGUNAAN E-MONEY DENGAN TINGKAT KONSUMSI MAHASISWA (Studi Pada Mahasiswa Universitas Samawa Sumbawa Besar) - Zulkifli Abdullah; U Usman (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of the use of electronic money (e-money) on the level of consumption of students at Samawa University Sumbawa Besar. The type of this study was associative. The type of data used is quantitative obtained from primary sources through a questionnaire. The population in this study were 619 students of the Faculty of Economics and Management. The sample determination was carried out using a purposive sampling technique so that the number of populations that met the requirements to become the research sample was 93 people. Data analysis is carried out with simple linear regression analysis techniques, partial hypothesis testing (T-test), and determinant coefficient test (R2). The results showed that the use of electronic money (e-money) had a positive and significant effect on the level of consumption of students at Samawa University Sumbawa Besar. The effect of the use of electronic money (e-money) on the level of consumption of students at Samawa University Sumbawa Besar is 10.1%, while the remaining 89.9% is influenced by other factors that are not examined in this study, such as income, product prices, tastes and education.